Complete Genome Sequences of Two Japanese Eel Endothelial Cell-Infecting Virus Strains Isolated in Japan - Naoi, Yuki (Genome Announc, 2015)
Japanese eel endothelial cell-infecting virus (JEECV) causes viral endothelial cell necrosis of eel (VECNE), resulting in severe economic losses in eel aquaculture in Japan. Here, we report the complete genome sequences of two new JEECV strains isolated from farmed Japanese eels.